Procedure of taking decisions in intellectual teaching systems with illegible aim functions - Шибицкая, Н. Н. (Proceedings of National Aviation University (archive), 1998)
Considered are structural methods of organization of the process of teaching in the system "operator-simulator". Proposed is a structural model of organization of the process of teaching with the use of algorithms of process analysis. In the given structure of knowledge we construct, on the basis of algorithm, the process of teaching on the given course. The formulation of knowledge presenting trajectory is exercised on the basis of receiving current results of learning the information by the operator. This enables us to give expert essesment of the activity during whole process of learning . This approach allows us to establish feedback in order to connect the trajectory of teaching